Percutaneous ethanol and calcitriol injection therapy for hyperparathyroidism – a single-centre experience - Leong, Eugene Kwong Fei; See, Ray Meng; Lin, Zhimin; Chin, Meredeth Choon Siang; Chew, Joshua Wei Yang; Ngiam, Kee Yuan; Lee, James Wai Kit (Frontiers in Endocrinology, 2025)
BackgroundThe purpose of this study is to evaluate the use of percutaneous ethanol and calcitriol injection therapy for hyperparathyroidism (HPT), while taking into account the efficacy, safety and feasibility as an ambulatory procedure alternative to surgical parathyroidectomy.MethodsWe included nine patients who underwent percutaneous injection therapy for HPT from January 2018 to December 2021 in our institution. They were followed up from date of first percutaneous injection until death or October 2022 (mean duration of 9.0 months).ResultsFour patients underwent percutaneous ethanol injection therapy (PEIT) (mean age 61.0 [31–89] years old), while the remaining five underwent percutaneous calcitriol therapy (PCIT) (mean age 62.6 [35–91] years old). The analyzed parameters are age, BMI, serum turn over markers as iPTH, Ca, alkaline phosphatase and vitamin D. Two out of the four patients undergoing PEIT had a successful outcome, although one needed to continue cinacalcet due to persistent serum calcium levels. Three out of five PCIT patients in our series had successful procedure, although one subsequently developed refractory disease.ConclusionPEIT and PCIT are feasible and safe therapeutic alternatives to surgical parathyroidectomy in HPT refractory to medical treatment, with postulated benefits of decreased costs and being an outpatient procedure. However, further studies are necessary to evaluate the efficacy and cost-effectiveness with these techniques prior to widespread adoption.